Molecular and Phenotypic Characterization of Phialemonium and Lecythophora Isolates from Clinical Samples - Perdomo, H. (American Society for Microbiology, 2011)
Several members of the fungal genera Phialemonium and Lecythophora are occasional agents of severe human and animal infections. These species are difficult to identify, and relatively little is known about their frequency in the clinical setting. The objective of this study was to characterize morphologically and molecularly, on the basis of the analysis of large-subunit ribosomal DNA sequences, a set of 68 clinical isolates presumed to belong to these genera. A total of 59 isolates were determined to be Phialemonium species (n = 32) or a related Cephalotheca species (n = 6) or Lecythophora species (n = 20) or a related Coniochaeta species (n = 1). Nine isolates identified to be Acremonium spp. or Phaeoacremonium spp. were excluded from further study. The most common species were Phialemonium obovatum and Phialemonium curvatum, followed by Lecythophora hoffmannii, Cephalotheca foveolata, and Lecythophora mutabilis.